Patient-reported outcomes and functional exercise capacity in a real-life setting in non-small cell lung cancer patients undergoing stereotactic body radiotherapy: the Lung PLUS study - van der Weijst, Lotte; Bultijnck, Renée; Van Damme, Axel; Huybrechts, Vincent; van Eijkeren, Marc; Lievens, Yolande (Frontiers in Oncology, 2023)
To better understand the impact of stereotactic body radiotherapy (SBRT) and its treatmentrelated toxicity on early-stage non-small cell lung cancer (ES-NSCLC) patients, we conducted the Lung PLUS study in a real-world setting. This is a monocentric prospective longitudinal study up to 12 months post-treatment, evaluating clinician-and patient-reported toxicity (resp. CTCAE and PRO-CTCAE), health-related quality of life (HRQoL) (EORTC QLQ-C30 and LC-13), activities of daily living (HAQ-DI) and functional exercise capacity (6 Minute Walking Test (6MWT)). A mixed model approach was applied to analyse the data. At baseline, clinicians and patients (n=51) reported mostly fatigue (63% vs 79%), cough (49% vs 75%) and dyspnea (65% vs 73%) of any grade. Dyspnoea (p=.041) increased over time. Meaningful clinical improvements were particularly seen in pain, fatigue, and cough. Clinician reported clinically meaningful improvements and deteriorations over time in fatigue, cough, and dyspnea. Almost at every timepoint, more people reported deterioration to the clinician than improvement in aforementioned toxicities. Overall HRQoL (p=.014), physical (p=.011) and emotional (p<.001) functioning improved over time. At baseline, patients had a moderate daily functioning score and walked an average distance of 360 meters. No statistically significant differences were found in daily functioning and exercise capacity over time.Our study showed an increase in patient-reported toxicity and dyspnoea, without impacting functional status, following SBRT. Overall HRQoL, physical and emotional functioning improved over time. Understanding the impact of treatment on patient-reported outcomes is crucial to identify the needs/problems of patients to enhance their HRQoL.